Evaluation of Southern African wild edible plants for potential herb-drug interactions through ex vivo p-glycoprotein and in vitro cytochrome P450 3A4 inhibitory effects - P.S. Kheoane; K.C. Mokhetho; S. Mokhele; K.C. Mbara; C.M. Leonard; T.H. Gadaga; C. Tarirai (Elsevier, 2025)
Background: Wild edible plants (WEPs) including herbs provide staple foods as well as income for local communities on the African continent. However, these commonly used plant materials interact with orthodox or conventional drugs through both p-glycoprotein (P-gp) and cytochrome P450 enzymes inhibition. Hence, it is vital to explore the possibility of herb-drug interactions when concomitantly taking conventional drug dosage forms with some of the WEPs. P-gp and CYP3A4 show analogous substrate specificities and work together to establish an intestinal absorption barrier against xenobiotics. This study investigated the ex vivo p-glycoprotein inhibition and the in vitro inhibition of cytochrome P450 3A4 (CYP3A4) isoezyme by selected wild edible plants to identify potential food/herb-drug interactions. Methods: Ethanolic extracts of 30 wild edible plants sourced from Lesotho, Eswatini and the Limpopo province of South Africa were used for the study. Drug transport studies using propranolol, a P-glycoprotein substrate, across porcine intestinal tissue were conducted using intestinal sacs with test solutions in Krebs-Ringer bicarbonate buffer (pH 7.4) under a 95 % O2/5 % CO2 atmosphere. For the in vitro luminescent-based CYP3A4 inhibition assay, both porcine liver and intestinal microsomes were extracted from their respective tissues by homogenization, followed by high-speed centrifugation and standardization before use. Results: Sisymbrium thelungii O. E. Schulz significantly (p < 0.05) inhibited P-gp with an effective apparent permeability coefficient (Papp eff) of (7.53±0.33) × 10-6 cm/s and effective flux (Jeff) of 1.38±0.01 µg/cm2/min which was similar to sodium orthovanadate (positive control), indicating potential for herb/food-drug interaction possibly by absorption enhancement of poorly permeable P-gp substrates by this plant. Additionally, both Rubus cuneifolius Pursh and Hypoxis hirsuta (L.) Coville had significant (p < 0.05) p-glycoprotein inhibitory effects with Papp eff of (6.60±0.52) × 10-6 cm/s and Jeff of 1.11±0.08 µg/cm2/min, and Papp eff of 6.58±0.67 × 10-6 cm/s and Jeff of 1.19±0.12 µg/cm2/min, respectively. Significantly (p < 0.05), Rubus cuneifolius at a concentration of 0.2 mg/mL exhibited the strongest CYP3A4 inhibition in liver microsomes suggesting its potential as a bioavailability enhancer of CYP3A4 substrates. Meanwhile, Wahlengergia androsacea A.DC exhibited the most significant (p < 0.05) CYP3A4 inhibitory effect at the same concentration in intestinal microsomes. Conclusion: The observed inhibitory effects of certain wild edible plants on P-gp-mediated drug efflux and CYP3A4 drug metabolism indicate potential food/herb-drug interactions challenges for clinical practice. The herb/food-drug interactions also present opportunities for discovery of new functional excipients for enhancing the permeability of poorly absorbed orally administered drugs that are substrates of P-gp and CYP3A4.